Comparison of Soil Organic Carbon Dynamics in Forested Riparian Wetlands and Adjacent Uplands. Issue 5 (29th August 2014) - Ricker, Matthew C.; Stolt, Mark H.; Zavada, Michael S.
Abstract : Wetland riparian soils typically have greater C pools than adjacent uplands, yet quantifying soil organic C (SOC) sequestration in riparian systems remains difficult. Quantification of major inputs and losses of autochthonous SOC through process‐based measurements would allow for better comparisons between riparian and upland systems. In this study, we quantified major soil C fluxes within five paired headwater riparian and upland sites in Rhode Island. The difference between total C inputs and losses were used to construct net annual landscape‐scale SOC sequestration rates. Annual SOC inputs were statistically similar between landscapes, with the exception of those from understory herbaceous vegetation, which were significantly greater ( p < 0.001) in riparian zones than uplands. Mean annual C losses via soil respiration were also statistically similar between landscapes, but estimates of microbial respiration (actual loss of SOC) were significantly less ( p < 0.01) in riparian ecosystems. Thus, riparian forests had greater net annual SOC sequestration (range 2.4–3.4 Mg C ha −1 yr −1 ) than paired upland sites (range 0.4–2.1 Mg C ha −1 yr −1 ). Our results suggest that process‐based SOC sequestration measures can yield similar results to traditional methods, such as chronosequences, but our averaged estimates (2.0 Mg C ha −1 yr −1 ) were greater than those typically reported using alternate approaches.